2016
DOI: 10.1016/j.phymed.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer cells are sensitive to Lanatoside C induced cell death independent of their PTEN status

Abstract: a b s t r a c tBackground: Hepatocellular carcinoma is the second deadliest cancer with limited treatment options. Loss of PTEN causes the P13K/Akt pathway to be hyperactive which contributes to cell survival and resistance to therapeutics in various cancers, including the liver cancer. Hence molecules targeting this pathway present good therapeutic strategies for liver cancer. Hypothesis: It was previously reported that Cardiac glycosides possessed antitumor activity by inducing apoptosis of multiple cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Digoxin was found to inhibit several types of cancer cells, such as breast cancer, lymphoma, melanoma, myeloma, and small cell lung cancer 3638 . Lanatoside C was also demonstrated to inhibit tumor growth, such as colorectal cancer and human hepatocellular carcinoma 3941 . For synergistic cancer therapy, lanatoside C combined with TRAIL-secreted neural stem cells can target glioblastoma 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin was found to inhibit several types of cancer cells, such as breast cancer, lymphoma, melanoma, myeloma, and small cell lung cancer 3638 . Lanatoside C was also demonstrated to inhibit tumor growth, such as colorectal cancer and human hepatocellular carcinoma 3941 . For synergistic cancer therapy, lanatoside C combined with TRAIL-secreted neural stem cells can target glioblastoma 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these compounds on cell cycle protein expression is more pronounced on Huh7 cells ( Figure 5B). Mahlavu cells are reported as more resistant to small molecule inhibitors due to PTEN deletion in PI3K/Akt signaling pathway [25]. The effect of the compounds can still be observed even in these cells.…”
Section: Characterization Of Cell Death Mechanism Induced By Boehmerimentioning
confidence: 99%
“…Huh7 and Hep3B cells carry epithelial features, whereas Mahlavu and SNU-475 cells carry migratory mesenchymal-like properties. 6,7 Furthermore, Huh7 and Hep3B cells differ in their p53 gene status: Huh7 cells express p53IJY220S), but Hep3B cells are null for the TP53 gene. There-fore, the expression of mutant p53 causes differential activation of the β-catenin protein and its downstream mesenchymal proteins such as E-cadherin, vimentin, snail and slug.…”
Section: Csc Marker Expression Varies Among Cell Lines Of Hcc Sincementioning
confidence: 99%
“…It was shown that Mahlavu and SNU-475 cells have constitutively active Akt protein due to loss of the PTEN tumor suppressor. 7 Current studies and clinical trials focus on the anti-CSC compounds targeting extracellular mediators or cell surface molecules as well as molecules involved in EMT and metastasis. 8 Thus, it is crucial to define which marker is efficient to detect and analyse cancer stem cell markers in each cell line, which we studied by flow cytometry.…”
Section: Introductionmentioning
confidence: 99%